Idiopathic chronic intestinal pseudo-obstruction syndrome is strongly associated with low serum levels of vitamin D - Panarese, Alba; Dajti, Elton; Eusebi, Leonardo Henry; Vestito, Amanda; Zagari, Rocco Maurizio (European journal of gastroenterology & hepatology, 2024)
Idiopathic chronic intestinal pseudo-obstruction (CIPO) is associated with intestinal inflammation and malabsorption and may cause serum vitamin D deficiency. We aimed to assess whether there is an association between idiopathic CIPO and serum levels of 25-hydroxy-vitamin D. Consecutive patients with confirmed diagnosis of idiopathic CIPO were prospectively enrolled and matched with healthy controls by gender, age, and BMI. Median serum level of 25-hydroxy-vitamin D of patients with CIPO was compared with that of healthy subjects using the Wilcoxon signed-rank test for matched samples. A total of 35 patients with CIPO and 35 matched healthy subjects were enrolled. All patients with CIPO had a 25-hydroxy-vitamin D deficiency with serum levels <12 ng/ml. The median serum level of vitamin D was significantly lower in patients with CIPO than in healthy controls (5.7 vs. 29.7 ng/ml, P  < 0.0001). Serum level of vitamin D was not associated with gender ( P  = 0.27), age ( P  = 0.22), BMI ( P  = 0.95), high (>10 000 × ml) WBC count ( P  = 0.08), or high (>5 mg/l) C-reactive protein ( P  = 0.87) among patients with CIPO. CIPO seems to be strongly associated with low serum levels of 25-hydroxy-vitamin D.